hope that this answers your problem !
To solve this question, we first need to layout the equation
-2 1/2 -(-1 3/4)
Step 1
-2 1/2-(-1 3/4) ... Equation
Step 2
5/2-(-1 3/4) ... Converted to improper fraction
Step 3
5/2-(-7/4) ... converted to improper fraction
Step 4
5/2--7/4 ... Got rid of parenthesis
Step 5
-3/4 ... Subtract
Answer:
-3/4 ... Answer
So the answer for this problem is C, -3/4
Answer:
2·(a^2 + b^2) = (a + b)^2
2·a^2 + 2·b^2 = a^2 + 2·a·b + b^2
a^2 + b^2 = 2·a·b
a^2 - 2·a·b + b^2 = 0
(a - b)^2 = 0
a = b
Answer:
Step-by-step explanation:
y=-\frac{1}{2}x+\frac{11}{2}
Answer:36 times hope it helps
Step-by-step explanation:
Answer:
The slope is y=0.59x so 0.59
The y intercept is 0